Inhalants - Weatherly, Myra. (Springfield, N.J. : Enslow Publishers, Inc., 1996)
Discusses some of the chemical substances which people inhale for a quick high, the dangers of "huffing," the toxic effects of such substances, and social aspects of inhalant abuse.
Includes bibliographical references (p. 95-105) and index.
Keywords: Inhalant abuse -- Juvenile literature; Inhalant abuse; Substance abuse